Inorganic waste management at Alila Villas Uluwatu, Bali - Ilmiyah, Sulfa; Dalem, A.A.G. Raka; Muksin, I Ketut (Jurnal Biologi Udayana, 2021)
Environmental problems are complex things that they are very influential on all components in the ecosystem. One of the environmental problems is caused by the production of waste that is not treated properly, for example in the hotel industry. Tourism is one of the activities that produce various kinds of waste, both environmentally friendly and not. Products that are not environmentally friendly can pollute the environment if they do not handled properly. Alila Villas Uluwatu (AVU) is one of hotels in Bali that are committed to environmentally friendly and efforts to protect the environment by minimizing waste production. The objective of this research was to find out AVU's strategies in protecting the environment, especially in handling the resulting inorganic waste, such as glass, paper and plasctics. The method utilized in data collection on this study was through conducting interview, direct observation in the field and examination of related documents. Data analysis was performed descriptively, either in  qualitative and quantitative forms. The results showed that the waste management strategy in AVU included efforts to minimize inorganic waste production and by using more environmentally friendly materials such as toothbrushes with wooden handles, paper straws and bamboo straws.